EEG alpha power and coherence time courses in a sustained attention task - DOCKREE, PAUL MICHAEL; REILLY, RICHARD; ROBERTSON, IAN (IEEE, 2003)
Alpha activity at certain brain regions and the functional relationships between these regions quantified by alpha coherence were examined in a fixed sequence Sustained Attention to Response Task (SART), which involves the withholding of key presses to rare targets. The effects of distinguishing smaller sub bands within the alpha band to explain distinct cognitive components are assessed. It was found that in two of three subjects average power in the alpha-1 band was phasically related to stimulus presentation, possibly reflecting short-term attentional processes. Also in two of the three subjects, average power in the alpha-2 band showed a relatively slow desynchronisation approaching the rare target, possibly reflecting expectancy.
IEEE International Conference on Neural Engineering
PUBLISHED
Keywords: Alpha activity; EEG coherence